Semiotic Analysis in Instagram Logo - Eva Eriva Tandi Payuk; Zakrimal Zakrimal (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
This article investigated about semiotic that found in instagram logo. This article used Instagram, because many people nowadays used Instagram to express their selves.  The aim of this study was to find out the connotative and denotative meaning through the instagram. The researcher used John theory to reveal this study. In this research, the researcher applied the qualitative descriptive method. The method of collecting data was observation. The object of this research was the instagram logo. The result is there are twelve data that has meaning from different logo on Instagram. They all have different functions based on the logo. The conclusion is Instagram as a social media app that allows users to share photos and videos, add captions, edit filters, engage with others, and explore the world by using this application.